Promoting multiculturalism: Teachers’ English proficiency and multicultural education in Indonesia - Diem, Chuzaimah Dahlan; Abdullah, Umar (Universitas Pendidikan Indonesia, 2020)
Greater disparities and inadequacies of English proficiency (EP) may influence the educational process for EFL teachers of different cultural backgrounds. This study aims at describing the condition of 104 English as a Foreign Language (EFL) teachers’ EP in the Southern Region of Sumatra in relation to such variables as education level (EL), cultural backgrounds, teaching assignment level, and gender. Using English test scores of teachers’ teaching status (pre-service and in-service), EL, gender, multicultural education questionnaire, and teaching assignment, teachers’ EP is described. This study reveals that EL affects EP and also becomes the best predictor of their cultural knowledge and experience, such as personal development, leadership, curriculum instruction, general sensitivity, and cultural awareness. Furthermore, teachers teaching at higher levels of education appear to be better in EP than those teaching at lower levels, and in-service teachers are also better than pre-service teachers in their teaching responsibility. Although there is no difference in gender in their EP as a whole, females’ EP, listening skill, and personal development are significantly correlated. The implication of the findings indicates that to be proficient in English and culturally developed with integrity, teachers must have at least a master’s degree in addition to having an in-service status of teaching employment.